Rain Attenuation at Tropical Region- Site Diversity Gain Models' Sensitivity - Fazdliana Samat; Mandeep Singh Jit Singh (IAES Indonesian Section, 2019)
Rain is the major impairment to the signal propagation from satellite to earth. The signal that brings an important data might be lost in a sudden due to heavy rainfall especially in the region with tropics climate. The undesirable effect mainly occurred at above of 10 GHz signal frequency which is expected to bring more data compared to a lower frequency. One of the possible solutions that was proven to be effective to overcome this impairment is the implementation of site diversity. The empirical model that has been developed to measure the effectiveness of the diverse site is yet to be finalized in tropical region. This article compares ITU-R, Hodge, Panagopoulos, Semire and Yeo Model to observe their sensitivity to the major factors that contributes to the site diversity gain such as frequency, site separation distance, elevation angle and baseline orientation angle. These major factors are used as input to the models. The default factors’ value was set to 20.2 GHz frequency, 68.8° of elevation angle, 42.52 km site separation distance and 65° of baseline angle. The factors were interchangeably with 12.255 GHz frequency, 25° of elevation angle, 10 km distance and 4° of baseline angle, which created 16 sets of combinations. The percentages of increment or decrement of the gain predicted by each model with respect to the default parameter were calculated. In overall, each model has their own discrepancy towards these factors and a more dynamic model should be developed to improve the weaknesses.Rain is the major impairment to the signal propagation from satellite to earth. The signal that brings an important data might be lost in a sudden due to heavy rainfall especially in the region with tropics climate. The undesirable effect mainly occurred at above of 10 GHz signal frequency which is expected to bring more data compared to a lower frequency. One of the possible solutions that was proven to be effective to overcome this impairment is the implementation of site diversity. The empirical model that has been developed to measure the effectiveness of the diverse site is yet to be finalized in tropical region. This article compares ITU-R, Hodge, Panagopoulos, Semire and Yeo Model to observe their sensitivity to the major factors that contributes to the site diversity gain such as frequency, site separation distance, elevation angle and baseline orientation angle. These major factors are used as input to the models. The default factors’ value was set to 20.2 GHz frequency, 68.8° of elevation angle, 42.52 km site separation distance and 65° of baseline angle. The factors were interchangeably with 12.255 GHz frequency, 25° of elevation angle, 10 km distance and 4° of baseline angle, which created 16 sets of combinations. The percentages of increment or decrement of the gain predicted by each model with respect to the default parameter were calculated. In overall, each model has their own discrepancy towards these factors and a more dynamic model should be developed to improve the weaknesses.